2006
DOI: 10.1158/0008-5472.can-05-2961
|View full text |Cite
|
Sign up to set email alerts
|

Aggresome Disruption: A Novel Strategy to Enhance Bortezomib-Induced Apoptosis in Pancreatic Cancer Cells

Abstract: The proteasome inhibitor bortezomib ( formerly known as PS-341) recently received Food and Drug Administration approval for the treatment of multiple myeloma, and its activity is currently being evaluated in solid tumors. Bortezomib triggers apoptosis in pancreatic cancer cells, but the mechanisms involved have not been fully elucidated. Here, we show that pancreatic cancer cells exposed to bortezomib formed aggregates of ubiquitin-conjugated proteins (''aggresomes'') in vitro and in vivo. Bortezomib-induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
209
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(220 citation statements)
references
References 50 publications
9
209
0
2
Order By: Relevance
“…Candidates include inhibition of nuclear factor-nB (39,46), p53 activation (18), production of reactive oxygen species (47 -49), and the accumulation of misfolded and/or damaged proteins resulting in a phenomenon termed ''endoplasmic reticulum stress'' (50 -54). With respect to the latter, our group and another found that, like tumor necrosis factor -related apoptosis-inducing ligand, histone deacetylase inhibitors synergize with bortezomib to promote cell death by enhancing the effects of bortezomib on endoplasmic reticulum stress (51,52).…”
Section: Discussionmentioning
confidence: 98%
“…Candidates include inhibition of nuclear factor-nB (39,46), p53 activation (18), production of reactive oxygen species (47 -49), and the accumulation of misfolded and/or damaged proteins resulting in a phenomenon termed ''endoplasmic reticulum stress'' (50 -54). With respect to the latter, our group and another found that, like tumor necrosis factor -related apoptosis-inducing ligand, histone deacetylase inhibitors synergize with bortezomib to promote cell death by enhancing the effects of bortezomib on endoplasmic reticulum stress (51,52).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, prolonged exposure of HuT-102 cells to PS-341 resulted in accumulation of mono-and poly-ubiquitylated endogenous Tax (Figure 6g). Upon proteasome inhibition, poly-ubiquitylated proteins are targeted by the histone deacetylase 6 to aggresome-mediated degradation (Nawrocki et al, 2006). We found that stabilization of poly-ubiquitylated Tax was significantly enhanced by the co-treatment with PS-341 and the histone deacetylase inhibitor, valproic acid and was maintained in the presence of cycloheximide (Figure 6g).…”
Section: Tax Induces Perinuclear Delocalization Of Endogenous Ikk Submentioning
confidence: 88%
“…In multiple myeloma (83), mantle cell lymphoma (38), CML (83), and non-small cell lung cancer (21), oxidative stress is seen with the boretzomib=vorinostat combination. Reports of synergistic cell death extend to additional cell-line models including pancreatic cancer (76), hepatomas (25), and MDS (30). Aside from bortezomib, other proteasome inhibitors such as NPI-0052 also synergize with HDAC inhibitors.…”
Section: Combinations Of These Agentsmentioning
confidence: 99%